(untitled) (Revista de Ciências Agroveterinárias, 2006)
Medicinal plants are natural resources considered by the World Organization of Health, strategic for the purpose of obtaining more health and quality of life for the populations. To reach this purpose, the present article tries to open the debate about the construction of a transformation way, based on the human being’s integral vision and consequently of the collective health starting from the transdisciplinarity. In such a way, that it can collaborate to revert the crisis of values that reaches our ambient and threat the life, being revealed as a contribution in the sense of crossing old values established in the disciplinarity and in the reductionism, understanding that these, impede progresses of the integration in the area of medicinal plants.